PENINGKATAN KEMAMPUAN MENULIS CERPEN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN SINETIKA DENGAN TEKNIK MENULIS BERANTAI SISWA KELAS X SMA NEGERI 1 NA. IX-X TAHUN PELAJARAN 2019/2020 - ANNIM HASIBUAN (JURNAL ILMIAH MAKSITEK, 2020)
The problem in this study is: (1) How does the learning process of creative writing of grade X students SCHOOL through theimplementation of a synethic model learning with serial writing techniques?; (2) is learning the model of synetics with chainwriting techniques can improve the creative writing skills of grade X SMA Negeri 1 Na. IX-X year lesson 2019/2020? Theobjectives in this study are: (1) to describe the learning process of creative writing of grade X students in high school throughthe application of the study of synethic models with serial writing techniques; (2) to describe whether learning of a synethicmodel with a serial writing technique can improve the creative writing skills of high school class class X students 1 Na. IX-Xlesson year 2019/2020. The method used in research is the method of research action Class (PTK). Where this researchaims to obtain an overview of the influence of the model of the learning of synethics with serial writing techniques to theability to write short stories of SMA Negeri 1 Na. IX-X year lesson 2019/2020. The subject in this study was a grade X highschool student numbering 40 people. While the object in this study is the result of writing short stories of students. Theinstrument used in data collection is a test essay, where the student is told to write a short story according to the criteria thathad been described by the previous researcher. The results showed that "learning the model of synethics with chain writingtechniques can improve the creative writing skills of class X SMA Negeri 1 Na. IX-X Learning year 2019/2020 areacceptable.